2021
DOI: 10.1016/j.ijid.2020.12.065
|View full text |Cite
|
Sign up to set email alerts
|

High SARS-CoV-2 IgG/IGM seroprevalence in asymptomatic Congolese in Brazzaville, the Republic of Congo

Abstract: Introduction: The Republic of the Congo detected its first case of coronavirus disease 2019 (COVID-19) on March 14, 2020, and within several weeks, the country had introduced protective measures that were still in force in July 2020. Over the course of time, the progression in the number of clinical cases has appeared to be lower than expected, although reverse transcription polymerase chain reaction (RT-PCR) testing has been somewhat limited. In order to evaluate the incidence of severe acute respiratory synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
4
16
0
1
Order By: Relevance
“… 17 , 18 , 19 Two were conducted in each of the following countries: Republic of South Africa, 20 , 21 Ethiopia, 22 , 23 Libya 24 , 25 Kenya 26 and Democratic Republic of Congo (DRC). 27 One study was conducted in each of the following countries: Malawi, 28 Togo, 29 Ivory Coast, 30 Zambia, 31 Egypt, 32 Gabon, 33 Congo Brazaville, 34 South Sudan, 35 Cameroon 36 , 37 and Guinea Bissau. 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 , 19 Two were conducted in each of the following countries: Republic of South Africa, 20 , 21 Ethiopia, 22 , 23 Libya 24 , 25 Kenya 26 and Democratic Republic of Congo (DRC). 27 One study was conducted in each of the following countries: Malawi, 28 Togo, 29 Ivory Coast, 30 Zambia, 31 Egypt, 32 Gabon, 33 Congo Brazaville, 34 South Sudan, 35 Cameroon 36 , 37 and Guinea Bissau. 38 …”
Section: Resultsmentioning
confidence: 99%
“…The study participants in 10 studies were recruited from the general population, 18 , 22 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 four studies were from health workers, 17 , 27 , 28 , 38 one study combined health workers and community, 25 one study combined health workers, air transport, police and drivers, 29 three studies recruited blood donors, 19 , 20 , 39 one study recruited water front workers, 21 one study involved travelers, 40 one study recruited drivers and their assistants, 26 while the other one recruited gold miners. 30 All studies were conducted in the period between April 2020 and April 2021 except one study by Olayanju et al.…”
Section: Resultsmentioning
confidence: 99%
“…In a serosurvey conducted in Brazzaville, Congo, in the period April-July 2020, anti-SARS-CoV-2 antibodies were detected in 15% of the sampled adults. 13 In Guilan region of Iran, 22% of study participants enrolled in April 2020 had antibodies. 14 A larger national study in Iran conducted between April and June 2020 reported a 17% seroprevalence rate.…”
Section: Discussionmentioning
confidence: 99%
“…National case rates were obtained from Our World in Data (16). Sub-national case rates were calculated from sub-national reported case counts and population data (14,15,19,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Methodsmentioning
confidence: 99%
“…Because serostudy data in AFRO are sparse, both national estimates and sub-national estimates were included (14,(18)(19)(20)(21)(22). National case rates were obtained from Our World in Data (16).…”
Section: Methodsmentioning
confidence: 99%